2016
DOI: 10.7448/ias.19.1.20520
|View full text |Cite
|
Sign up to set email alerts
|

Safety of combination antiretroviral prophylaxis in high‐risk HIV‐exposed newborns: a retrospective review of the Canadian experience

Abstract: IntroductionThe optimal management of infants born to HIV-positive mothers who are untreated or have detectable viral load prior to delivery remains controversial. Despite the increasing use of combination antiretroviral therapy (cART) for post-exposure prophylaxis (PEP) of neonates at high risk of HIV infection, there is little safety and pharmacokinetic data to support this approach. The objective of this study was to evaluate the safety and tolerability of cART for PEP in HIV-exposed neonates.MethodsRetrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…For infants born to ART‐naïve women, or where drug resistance is unlikely, zidovudine, lamivudine and nevirapine is a well‐tolerated combination regimen with the most clinical experience [18,19,21–24] (see Appendix for dosing).…”
Section: Neonatal Managementmentioning
confidence: 99%
“…For infants born to ART‐naïve women, or where drug resistance is unlikely, zidovudine, lamivudine and nevirapine is a well‐tolerated combination regimen with the most clinical experience [18,19,21–24] (see Appendix for dosing).…”
Section: Neonatal Managementmentioning
confidence: 99%
“…ZDV and didanosine (ddI), drugs that were introduced in the 1990s have only recently shown associations with congenital cardiac defects and cancer, [51,52] respectively, which would not have been apparent without many years of data. Given the changing drugs and changing populations without safety data from clinical trials, ongoing ARV safety surveillance in pregnancy is clearly needed.…”
Section: In-utero Antiretroviral Therapy Exposurementioning
confidence: 99%
“…HIV-positive pregnant women who consented to the cohort were prospectively followed during pregnancy, and their infants until age 18. This cohort has yielded important information regarding the safety of ART exposures both prenatally and in the postnatal period, including extensive laboratory and lymphocyte measures in HEU children through 24 months of age [51]. …”
Section: Art Safety Surveillance Programsmentioning
confidence: 99%
“…In a retrospective multicentre Canadian study involving 148 infants at high risk for MTCT receiving CNP using therapeutic doses and 145 infants at low risk receiving ZDV, haematological and growth parameters at birth and at 1 and 6 months of age were evaluated. The authors concluded that CNP was generally well tolerated, but reported that 10.2% of the CNP group had potential treatment‐related adverse effects (nonspecific signs and symptoms, including rash, vomiting, diarrhoea and irritability) versus none of the ZDV monotherapy recipients; furthermore, treatment was discontinued more frequently in the CNP group.…”
Section: Discussionmentioning
confidence: 99%